Proximal tubular RAGE mediated the renal fibrosis in UUO model mice via upregulation of autophagy - Bohao Liu; Tianshi Sun; Huiling Li; Shuangfa Qiu; Yijian Li; Dongshan Zhang (Cell Death and Disease)
Abstract Previous studies reported that RAGE participated in the process of kidney fibrosis, but the function and regulation pathway of RAGE in proximal tubular cells in this process remains unclear. Here, we found that expression of RAGE was increased by TGF-β1 treatment and unilateral ureteral obstruction (UUO). Knock down of RAGE ameliorated renal fibrosis by TGF-β1 treatment, the expression of vimentin, Collagen I&III, and fibronectin are decreased. Mechanistically, RAGE mediated TGF-β1-induced phosphorylation of Stat3 and directly upregulated the Atg7 to increase the level of autophagy, and ultimately resulting in renal fibrosis. Furthermore, PT-RAGE-KO mice reduced kidney fibrosis in UUO model via inhibiting Stat3/Atg7 axis by knocking down RAGE. Furthermore, the above findings were confirmed in kidney of patients with obstructive nephropathy. Collectively, RAGE in proximal tubular cells promotes the autophagy to increase renal fibrosis via upregulation of Stat3/Atg7 axis.